Phosphoinositide 3-kinase δ activity in patients with systemic lupus erythematosus - Mirfazeli, Elham Sadat; Kharkar, Shalmalee; Tsang-A-Sjoe, Michel W. P.; Papapietro, Olivier; Niewczas, Izabella; Parra Sanchez, Agner R.; Chandra, Anita; Okkenhaug, Klaus; Bultink, Irene E. M.; Mebius, Reina E.; Clark, Jonathan; Voskuyl, Alexandre E.; et al. (Frontiers in Immunology, 2026)
IntroductionNew biomarkers are needed for better stratification and personalized treatment of Systemic Lupus Erythematosus (SLE). Phosphoinositide 3-kinase δ (PI3Kδ) has been implicated in SLE pathogenesis. Here, we investigated whether a subset of SLE patients has increased PI3Kδ activity after T cell activation.MethodsT cells were isolated from frozen PBMCs of 108 SLE patients, 19 healthy controls, and one patient with Activated PI3K Delta syndrome (APDS), which provided a benchmark of increased PI3Kδ activity. After 90-minute anti-CD3/CD28 stimulation, phosphatidylinositol 3,4,5-trisphosphate (PIP3) and phosphatidylinositol 4,5-bisphosphate (PIP2) were measured using high-performance liquid chromatography-mass spectrometry.ResultsHigher levels of PIP3 (measured as the ratio of PIP3/PIP2) in stimulated T cells distinguished APDS patient from other subjects providing a useful biomarker of increased PI3Kδ activity. We observed no significant difference in T-cell PIP3 levels between SLE patients and healthy controls. However, a subset of SLE patients (n = 4) exhibited strong upregulation of PIP3 following T-cell stimulation, comparable to that observed in the APDS patient. PIP3 levels in stimulated T cells positively correlated with the frequency of CD4+ T cells and negatively correlated with the frequencies of CD8+, EMRA CD4+, and EMRA CD8+ T cells.ConclusionsWe describe the range of variation of PI3Kδ activity in T cells from a large cohort of patients with SLE and from healthy subjects. Our findings suggest that increased PI3Kδ activity is not associated with SLE in general, although some SLE patients exhibit a particularly strong upregulation of PIP3 levels after T-cell stimulation. This subgroup of SLE patients warrants further investigation given the promising effect of PI3Kδ inhibitors in restoring normal immune regulation.